THE EFFECT OF WIRELESS HEADPHONES ON THE CENTRAL NERVOUS SYSTEM - Yuldasheva F. U; Rustamova G.; Nazirjonov D.; Toirzhonov Zh.; Akbarova M.; Mansurkhozhaeva R. (Web of Journals Publishing, 2025)
In recent years, wireless headphones have become an integral part of everyday life, greatly simplifying the use of audio devices and providing mobility. However, the growing popularity of these devices raises questions about the possible impact of their operation on the central nervous system (CNS). Research shows that radio frequency radiation and prolonged use of headphones can cause cognitive, emotional and physiological changes. In this regard, studying the impact of wireless headphones on the CNS is becoming an urgent scientific task that is important for health care and the prevention of possible risks.
Keywords: Wireless headphones, electromagnetic radiation, Bluetooth headphones, central nervous system.